Nuclearization of Iran; the Policy of China - Islam, Thowhidul (Richtmann Publishing, 2011)
Iranian nuclear program has become a political discussion of significance in both Iran and western countries. Iran claims thatit is entitled to nuclear sovereignty over civilian nuclear power and has denied that it has had a nuclear weapons program, while westerngovernments feel the peaceful nuclear program has hidden intension of nuclear weapons. The international mediators have been makingreconciliatory efforts with Iran but have met with little success. In the face of these past failures and present challenges, China, a memberof UN Security Council, could be forced to consider acting with the other major powers to curb Iran’s nuclear ambition. On one hand,China has been increasingly supportive of the nonproliferation of weapons of mass destruction, at the same time; China’s economic boomhas resulted in an energy thirst that is now affecting Beijing’s foreign policy. China’s rise has brought its multifaceted national interests tothe fore including securing cooperative relations with other major powers, developing peaceful relations with neighbors including Iran, andgaining access to reliable resources to sustain the nation’s growing economy. Thus Iran’s nuclear case presents China’s leaders todemonstrate their ability to balance their domestic interests with their international responsibilities as a growing global power. Under thecircumstances China’s support for Iran's nuclear program has become one of the most talked topics in the international arena. This articlemainly aims at discovering the main factors behind China’s support for Iran’s nuclear program. It also includes understanding Iran’snuclear motivations and aspirations with a view to calculate Beijing’s stand.